Productive and qualitative characteristics of strawberry genotypes in the Plateau of the State of Santa Catarina, Brazil - Zanin, Daniel Suek; Lima, Juliana Martins de; Santos, Marllon Fernando Soares dos; Tillwitz, Katiana Vanusa; Fagherazzi, Antonio Felippe; Richter, Adrik Francis; Kretzschmar, Aike Anneliese; Rufato, Leo (Revista de Ciências Agroveterinárias, 2020)
To produce strawberries on a commercial scale, it is necessary to choose the cultivars best adapted to the growing site. This work aimed to compare strawberry genotypes regarding production and fruit quality, in the municipality of Lages, State of Santa Catarina, Brazil, during the 2017/2018 harvest season. In this work, 15 genotypes were evaluated, five commercial cultivars and ten advanced selections. The experimental design was in randomized blocks, with four replicates and plots of 11 plants. The cultivation system used was in the soil of an open field, in beds of approximately 90 centimeters, with three rows per bed. Planting distance was of 30 centimeters between rows and plants. The Sabrina cultivar showed the highest production (1,231.77 g plant-1) and number of fruits (78.48 fruits plant-1). The highest quality fruits were obtained from the selections FRF PIR 256.4, FRF 104.1, FRF 57.6, FRF LAM 119.1 and cultivar Pircinque, characterized by soluble solids/titratable acidity ratios above 15. In the productive cycle in question, cultivar Sabrina presented the best performance, demonstrating the potential for recommendation to the producers of the South Plateau of State of Santa Catarina.